Synergistic effect of ezetimibe addition on coronary atheroma regression in patients with prior statin therapy: Subanalysis of PRECISE-IVUS trial. (September 2016) - Tsujita, Kenichi; Yamanaga, Kenshi; Komura, Naohiro; Sakamoto, Kenji; Sugiyama, Seigo; Sumida, Hitoshi; Shimomura, Hideki; Yamashita, Takuro; Oka, Hideki; Nakao, Koichi; Nakamura, Sunao; Ishihara, Masaharu; et al.
Background: The IMPROVE-IT trial showed that the clinical benefit of statin/ezetimibe combination appeared to be pronounced in patients with prior statin therapy. We hypothesized that the antiatherosclerotic effect of atorvastatin/ezetimibe combination was pronounced in patients with statin pretreatment. Methods: In the prospective, randomized, controlled, multicenter PRECISE-IVUS trial, 246 patients undergoing intravascular ultrasound-guided percutaneous coronary intervention were randomized to atorvastatin/ezetimibe combination or atorvastatin alone. The dosage of atorvastatin was uptitrated with a treatment goal of lowering low-density lipoprotein cholesterol to below 70 mg/dl in both groups. Serial volumetric intravascular ultrasound was performed at baseline and 9–12 month follow-up to quantify the coronary plaque response in 202 patients. We compared the intravascular ultrasound endpoints in all subjects, stratified by the presence or absence of statin pretreatment. Results: The baseline low-density lipoprotein cholesterol level (100.7 ± 23.1 mg/dl vs. 116.4 ± 25.9 mg/dl, p  < 0.001) and lathosterol (55 (38 to 87)) µg/100 mg total cholesterol vs. 97 (57 to 149) µg/100 mg total cholesterol, p  < 0.001) was significantly lower, and campesterol/lathosterol ratio (3.9 (2.4 to 7.4) vs. 2.6 (1.5 to 4.1), p  < 0.001) was significantly increased in patients with statin pretreatment. Contrary to the patients without statin pretreatment (−1.3 (−3.1 to −0.1)% vs. −0.9 (−2.3 to 0.9)%, p  = 0.12), the atorvastatin/ezetimibe combination showed a significantly stronger reduction in delta percent atheroma volume, compared with atorvastatin alone, in patients with statin pretreatment (−1.8 (−3.6 to −0.3)% vs. −0.1 (−1.6 to 0.8)%, p  = 0.002). Conclusion: Compensatory increase in cholesterol absorption observed in statin-treated patients might attenuate the inhibitory effects of statins on coronary plaque progression. A low-dose statin/ezetimibe combination might be a promising option in statin-hyporesponder.